The PEMBERDAYAAN ORANG TUA DAN KADER DALAM PROGRAM INOVASI NASI KUNING ( INOVASI CEGAH STUNTING) DI DESA SIDOMULYO, KECAMATAN SELOREJO, KABUPATEN BLITAR - Suparni, Ita Eko (STIKES dan AKZI Karya Husada Kediri, 2026)
Stunting is a chronic nutritional problem that has long-term impacts on child growth and development as well as on the quality of human resources. Limited knowledge among parents of toddlers and posyandu cadres contributes significantly to the risk of stunting. This community service activity aimed to improve the knowledge and roles of parents and posyandu cadres in preventing and managing stunting through health education and the implementation of the Nasi Kuning Innovation Program (Stunting Prevention Innovation) in Sidomulyo Village, Selorejo District, Blitar Regency. The methods applied included health education on stunting, interactive discussions, and demonstrations of preparing toddler menus based on local food resources. Knowledge levels were evaluated using pre-test and post-test assessments. Participants consisted of parents of stunted toddlers and posyandu cadres. The results showed a significant improvement in participants’ knowledge after the intervention. The proportion of respondents with good knowledge increased from 8% in the pre-test to 76% in the post-test, while the low knowledge category was no longer observed. The Nasi Kuning Innovation Program served as an effective and practical nutrition education medium that encouraged active community participation in stunting prevention and management. This activity demonstrates that integrating health education with local food-based innovations is an effective approach to supporting community-based stunting reduction efforts.